Ending cyber coercion: Computer network attack, exploitation and the case of North Korea. Issue 2 (14th March 2016) - Whyte, Christopher
ABSTRACT: The use of coercive instruments of statecraft and military power to affect changes in strategic behavior is a common feature of international politics. Recently, a variety of state and sub-state actors have attempted to utilize cyber instruments of disruption and intrusion to bring about favorable outcomes. This article notes that digital instruments for coercion offer limited potential for effective compellent effect in world affairs. Nevertheless, as the case of North Korea's 2015 hack and (attempted) manipulation of Sony demonstrates, coercion using cyber weapons of intrusion and disruption is possible under particular conditions. In describing these conditions, I argue that the limits of cyber coercion should be seen more as a function of relevant social and institutional context than of the current state of technological possibilities. Technology certainly determines parameters of coercive interaction between actors, but success—and thus most determinants of strategic decisions surrounding cyber coercion—derives directly from sociopolitical context.